CAPACITY AND INSTITUTION BUILDING IN THE CIS IN REFUGEE AND HUMAN RIGHTS PROTECTION WITH EMPHASIS ON CENTRAL ASIA AND KAZAKHSTAN - Druke, Louise (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2000)
This study examines the capacity and institution building process, which started in the early nineties following the transformation of the Soviet Union into the Commonwealth of Independent States (CIS). The emphasis of this study is placed on an examination of progress made specifically in the refugee area, on the basis of the CIS Program of Action (POA) of the Regional Conference, to address the problems of refugees, displaced persons, other forms of involuntary displacement and returnees in the countries of the CIS and relevant neighbouring States in May 1996 and of the Central Asia South West Asia and Middle East (CASWAME) Action Plan of the Countries of the Central Asian Region in solving problems of asylum-seekers and refugees adopted at the Sub Regional Meeting in Bishkek in February 1998. Chapter 1 reviews progress, results and impact of the 1996 CIS Conference Program of Action on refugees and displaced persons, and reflects on the Meeting of June 1999 of the CIS Steering Group in the Follow-up of the Regional Conference. Chapter 2 examines developments and challenges in Central Asia with special emphasis on Kazakhstan following the opening of UNHCR Offices in the mid-nineties and the 1998 CASWAME action plan specifically conceming Afghan refugees. Chapter 3 analyses new opportunities for co-operation especially with the European Union (EU) and the Organisation of Security and Co-operation in Europe (OSCE) as well as the United Nations (UN), whose institutional support for national refugee capacity and institution building has been and will continue to be crucial. Chapter 4 explores the new EU approach toward refugee and migration policy and the action plans developed by the 1999 EU High Level Working group on Asylum and Migration, including Afghan refugees, in consultation with UNHCR.